The Summer of Broken Things - Haddix, Margaret Peterson (New York : Simon & Schuster/BFYR, 2018)
Fourteen-year-old Avery Armisted and sixteen-year-old Kayla Butts, once good friends, begrudgingly travel to Spain together for a summer vacation where they uncover a secret their families kept hidden from them their entire lives.
Keywords: Vacations -- Juvenile fiction; Families -- Juvenile fiction; Family secrets -- Juvenile fiction; Vacations -- Fiction; Families -- Fiction; Family secrets -- Fiction; Spain -- Juvenile fiction; Spain -- Fiction